MENINGKATKAN HASIL BELAJAR PASSING ATAS BOLA VOLI MELALUI PERMAINAN VOLSAL PADA SISWA SD - Lisa, Lisa; Hidasari, Fitriana Puspa; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract :Efforts to improve learning outcomes passing on volley ball through volleyball games directly targeted at students into focus the problems on this research. The method in this research include research on the subject, the research variables, the cycle of research, data and the method of data collection, data analysis techniques and indicators of success. This classroom action research subjects are 20 students.Results from studies of student learning outcomes in passing on through the game volsal in the first cycle with the lowest value of 50, the highest score of 92, the average value of 73 to the medium category, and classical completeness 50%. On the implementation of the second cycle of the data obtained with the lowest value of 67, the highest score of 92, the average value of 83 with good category, and classical completeness 90%, learning passingon studentoutcomes,reaching 80%.Â Keywords: volleyball, volleyball, passing, pasing on, volsal.